Psychosocial adjustment, spiritual well-being and associated factors among patients with spinal cord injury in Malaysia - Saharuddin, Danial Asyraf (2022)
Psychosocial adjustment is a required transition process from disabled to functioning states. People with spinal cord injury (SCI) stand facing a great challenge in psychosocial adjustment after the illness. However, this is less known among people with SCI in Malaysia. This study aims to examine the level of psychosocial adjustment and its associated factors in people with SCI who are receiving follow-up care at eight public hospitals one year after disability onset. This cross-sectional survey was conducted from December 2019 to November 2020 in University Malaya Medical Centre (UMMC), Sungai Buloh Hospital, Cheras Rehabilitation Hospital, Raja Permaisuri Bainun Hospital, Penang General Hospital, Sultan Ismail Hospital, Queen Elizabeth Hospital, and Sarawak General Hospital. Eligible respondents were 18 years old and above, sustained SCI and under active follow-up at least once in the past year at the participating centres. The questionnaire package, either in paper or online form, consisted of an information sheet, a consent form, and included the following measures. The psychosocial adjustment is represented primarily as the quality of life (QoL) measured by World Health Organisation Quality of Life (WHOQOLBREF), secondarily as the functional independence level by Spinal Cord Independence Measure – Self-rated (SCIM-SR), coping strategies by Brief Coping Orientation Problem Experienced (Brief COPE) comprises problemfocused, emotion-focused and dysfunctional-focused, quality of social support by Medical Outcome Study – Social Support Scale (MOS-SSS), and spiritual well-being which was by Functional Assessment of Chronic Illness Therapy - Spiritual (FACIT-Sp-12). Follow-up method were implemented to maximize the response rate. Data were cleaned, and missing data was replaced with multiple imputations, and analysed with multivariable analyses. The response rate was 61.3%, and after cleaning, imputation of missing data and exclusion of extreme outliers, 144 were included in the final analyses. Majority were males (68.8%), young adults (51.0%), Malay (59.7%), living with family (93.7%), completed basic education only (59.7%), unemployed (59.7%) and were on disability benefits (57.4%). Three-quarters had SCI of traumatic origins, mainly from motor vehicle accidents (56.1%) with 75.9% have paraplegia. The median duration after SCI are 7.0 years. The mean (SD) for the total WHOQOL-BREF was 52.9 (9.26), SCIM-SR 36.8 (17.23), Brief COPE: problem-focused 15.1 (3.70), emotionfocused 26.0 (5.30) and dysfunctional-focused 20.3 (5.05), Overall Support Index of MOS-SSS 58.1 (21.44) and FACIT-Sp-12 29.1 (8.24). It is observed that older age at diagnosis with SCI reported lower QoL (adjusted B -2.9, 95% CI - 5.45, -0.44). Dysfunctional-focused coping strategies had negative impact on QoL (adjusted B -0.48, 95% CI -0.80, -0.16). Oppositely, respondents with strong positive interaction support (adjusted B 0.07, 95% CI 0.00, 0.14), and higher sense of meaning and peace (adjusted B 0.57, 95% CI 0.28, 0.86) had higher health-related QoL. Psychosocial adjustment was observed to be relatively good in the current representative sample of SCI people in Malaysia, as represented by the QoL, moderate functional independence, quality social support, and spiritual well-being. The commonest coping method involves an emotional-focus coping strategy. Respondents who sustained SCI at a younger age, had more positive social interaction support, and had a strong sense of peace and purpose in life had a higher post-injury quality of life.